Effects of Post-Ruminal Urea Supplementation during the Seasonal Period on Performance and Rumen Microbiome of Rearing Grazing Nellore Cattle - Souza, Mailza Gonçalves de [UNESP]; Reis, Irene Alexandre [UNESP]; Carvalho, Isabela Pena Carvalho de; Porcionato, Marco Aurélio De Felicio; Prados, Laura Franco; Granja-Salcedo, Yury Tatiana; Siqueira, Gustavo Rezende [UNESP]; Resende, Flávio Dutra de [UNESP] (MDPI, 2022)
The objective was to evaluate the effects of urea with post-ruminal absorption in the supplementation of growing Nellore cattle reared on pasture during a seasonal period. For the study, two experiments were conducted. In experiment 1, rumen and blood parameters were evaluated using eight rumen-cannulated Nellore bulls with initial body weight (BW) of 763 ± 44 kg, distributed in a double Latin square 4 × 4. In experiment 2, 120 Nellore steers with initial BW of 380 ± 35 kg were used for performance evaluation, distributed in a randomized block design (blocking factor or initial BW). The evaluated treatments were 1: (TP-U) (control) = supplement with 24% crude protein (CP) containing urea as a source of non-protein nitrogen (NPN; 3%) and soybean meal, 2: (TP-PRU) = 24% CP supplement containing post-ruminal urea (PRU; 3.6%) and soybean meal; 3: (NPN-U-PRU) = 24% CP supplement containing urea + post-ruminal urea (U = 3% and PRU = 3.9%), without soybean meal; 4: (NPN-PRU) = supplement with 24% CP containing post-ruminal urea (7.5%), without soybean meal. The supplement was offered at 3 g/kg BW per animal, daily, once a day. All animals were kept on Urochloa brizantha cv. Marandu pasture. Statistical analyses were performed using the SAS PROC MIXED, and the data were evaluated by the following contrasts: C1 = TP-U/TP-PRU vs. NPN-U-PRU/NPN-PRU (Soybean meal replacement by NPN); C2 = TP-U vs. TP-PRU (conventional urea vs. post-immune urea); C3 = NPN-U-PRU vs. NPN-PRU (low and high post-ruminal urea-PRU level). The digestibility of dry matter, organic matter, and NDF was lower when soybean meal was replaced by non-protein nitrogen, also being different between the levels of post-ruminal urea used in the supplement. Ruminal pH was different when soybean meal was replaced by NPN (p = 0.003). Total concentration of short-chain fatty acids, concentrations of isobutyrate (p = 0.003), valerate (p = 0.001), and isovalerate (p = 0.001) were different, and blood urea was different when soybean meal was replaced by NPN (p = 0.006). Simpson’s diversity index was higher in the rumen of animals supplemented with TP-U than in those supplemented with TP-PRU (p = 0.05). A total of 27 phyla, 234 families, and 488 genera were identified. Nitrospirota and Gemmatimonadota phyla were detected just in the rumen of steers supplemented with TP-PRU. The performance (final BW, weight gain and gain per area) of the animals was different, being higher (p = 0.04) in animals supplemented with soybean meal, compared to NPN. The removal of soybean meal from the supplement and its replacement with either conventional urea plus post-ruminal urea or only post-ruminal urea compromises the performance of the animals. The lower the post-ruminal urea inclusion level, the lower the apparent digestibility of dry matter, organic matter, and NDF, when compared to animals supplemented with higher levels.
Keywords: non-protein nitrogen; recycling of nitrogen; rumen bacteria; true protein